El testamento del licenciado Cristóbal de Heredia, administrador de Góngora - De Paz, Amelia (El Colegio de México, 2013)
Transcript of an unpublished document (1626) meaningful to Gongora’s biography. With a brief introduction and an index of names (166 items).